Synthesis of stable Ti-containing mesoporous tubular membrane using silicalite-1 nanoparticles as seeds - Wang, X.; Meng, B.; Zhang, X.; Tan, X.; Liu, Shaomin (Elsevier BV, 2014)
Stable Ti-containing mesoporous membranes were successfully synthesized on different porous alumina tubes using nanosized Sil-1 particles as seeds by hydrothermal treatment, starting from sols having both CTABr and TPAOH structure directing agents. The samples were characterized by various techniques and tested in the gas permeation and hydroxylation reactions. The SEM images and XRD pattern detected a continuous membrane with well-ordered hexagonal mesoporous structure formed on the inner surface of ceramic tubes. Membranes prepared in the presence of zeolite nanocrystal seeds had zeolite structure units in the mesopore walls verified by FTIR, thus giving a better hydrothermal stability. The characterizations by EDX, XPS, FTIR and UV–Vis indicated that most of titanium in the growth solution was incorporated into the zeolite framework. Ti-containing mesoporous membranes prepared on the Sil-1 seeded support had larger proportions of tetrahedrally coordinated titanium, leading to better reaction activities and conversion rates. More Sil-1 nanoparticle seeds could promote more mesoporous zeolite to deposit on the support resulting in the formation of thicker mesoporous membrane. The gas permeation results confirmed that gas transport through the calcined mesoporous membrane was governed by Knudsen diffusion. Sil-1 seeding is a promising method to prepare high quality Ti-containing mesoporous membranes on porous ceramic tubes of different pore sizes.